Pengaruh Tingkat Pendidikan, Kompetensi Pedagogik, dan Motivasi Kerja terhadap Kinerja Guru - Robiatul Adawiyah (Universitas Indraprasta PGRI Jakarta, 2023)
Teachers are a component and make a huge contribution to the educational process, where teachers become professional staff who will determine whether the learning process is good, successful and of high quality. However, if the quality of the teacher is low and unable to complete the task well, then the teacher's performance in creating a successful educational process will be difficult. The aim of this research is to determine the influence of Educational Level, Pedagogical Competency, and Work Motivation on Teacher Performance. The approach used in this research is quantitative with a survey method through distribution using Google Form with the subjects were private high school teachers in East Jakarta in October-November 2022, and the sample in this research was 60 teachers. The data collection technique was a questionnaire arranged based on instrument variables with a Likert scale, then a Validity and Reliability Test process was carried out, then Hypothesis Testing used the t test and F test with significance. From the research results it is known that the independent variables together have a significant effect on the dependent variable (Teacher Performance). Partially, the Level of Education and Pedagogical Competency has a significant effect on Teacher Performance. Motivation does not have a significant effect on teacher performance.